The Influence of Perceived Risk and Trust on Interest in Visiting the Ubud Tourist Destination - Ni Putu Ratna Sari; Anak Agung Putri Sri; Anak Agung Gde Raka Dalem (International Journal of Social Science and Business, 2023)
During the two years of this pandemic, there has been an increasing sense of travel boredom. The reopening of various tourist attractions serves as a stimulus for tourists who want to enjoy the beauty of Bali again. With a special focus on Ubud, tourists express interest in exploring attractions, enjoying culinary experiences, and staying overnight. This study aims to comprehensively analyze the interaction between risk perception and beliefs related to tourists' intentions to visit Ubud. In addition, the study investigated the impact of risk perception on trust and subsequent influence on visiting intent, considering trust as a mediating variable. Quantitative analysis, using SEM Smart PLS, was performed on a sample of 100 individuals selected through accidental sampling. The results showed that risk perception had a negative impact on visiting intention and trust, while trust had a positive impact on visiting intent. This highlights the inverse relationship between risk and interest in visiting Ubud, with trust acting as a partial mediator. In conclusion, this study provides valuable insights into the dynamics of tourist behavior during the ongoing pandemic.